Comparative effectiveness of treatments to prevent dental caries given to rural children in school-based settings: protocol for a cluster randomised controlled trial. Issue 4 (13th April 2018) - Ruff, Ryan Richard; Niederman, Richard
Abstract : Introduction: Dental caries is the most prevalent childhood disease in the world and can lead to infection, pain and reduced quality of life. Multiple prevention agents are available to arrest and prevent dental caries; however, little is known of the comparative effectiveness of combined treatments when applied in pragmatic settings. The aim of the presented study is to compare the benefit of silver diamine fluoride and fluoride varnish versus fluoride varnish and glass ionomer therapeutic sealants in the arrest and prevention of dental caries. Methods and analysis: A longitudinal, pragmatic, cluster randomised, single-blind, non-inferiority trial will be conducted in low-income rural children enrolled in public elementary schools in New Hampshire, USA, from 2018 to 2023. The primary objective is to compare the non-inferiority of alternative agents in the arrest and prevention of dental caries. The secondary objective is to compare cost-effectiveness of both interventions. Caries arrest will be evaluated after 2 years, and caries prevention will be assessed at the completion of the study. Data analysis will follow intent to treat, and statistical analyses will be conducted using a significance level of 0.05. Ethics and dissemination: The standard of care for dental caries is office-based surgery, which presents multiple barriers to care including cost, fear and geographic isolation. The common intervention used in school-based caries prevention is dental sealants. The simplicity and affordability of silver diamine fluoride may be a viable alternative for the prevention of dental caries in high-risk children. Results can be used to inform policy for best practices in school-based oral healthcare. Trial registration: NCT03448107 . Pre-results.